SUPPORTIVE LEADERSHIP, SELF-AWARENESS, AND TEACHER PERFORMANCE: THE MEDIATING ROLE OF ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Fauzi, Fauzi; Jabani, Asrul (Fakultas Ekonomi dan Bisnis Universitas Alma Ata, 2024)
This study aims to investigate and understand the influence of supportive leadership and self-awareness on teacher performance, mediated by organizational citizenship behavior (OCB) in Wakatobi Regency. The research sample consists of 143 active teachers in Wakatobi Regency schools, selected purposively to reflect appropriate variation in the studied population, including various levels of experience and educational specialization. Stratified random sampling was conducted from schools with different educational levels and geographical locations. Data analysis used Structural Equation Modeling (SEM) with Partial Least Squares (PLS) as the main method. PLS was chosen for its ability to handle complex models with relatively small samples, allowing evaluation of direct and indirect relationships between the studied variables. The results show that OCB has a significant positive effect on teacher performance, indicating that teachers who are active in school activities beyond their formal duties tend to perform better. Self-awareness also has a significant positive effect on OCB and teacher performance, indicating that teachers who understand their strengths and weaknesses tend to be more active and perform better. Supportive leadership has a positive effect on OCB but is not directly significant on teacher performance. The indirect effects of self-awareness and supportive leadership through OCB on teacher performance are significantly positive. This study confirms the importance of OCB, self-awareness, and supportive leadership in improving teacher performance, and offers a basis for further research in teacher management and professional development.